Nationalism versus Universalism in Roque Cordero's Musical Journalism (Revista Argentina de Musicología, 2026)
This article analyzes the journalistic work and aesthetic thought of Panamanian composer Roque Cordero (1917–2008). Through a historiographical review of his texts published between 1952 and 1978, it examines the relationship between nationalism and universalism in his musical discourse. Cordero used journalism as a critical platform to ponder on the role of art, education, and professionalism in Panamanian musical endeavor, proposing that Panamanian music should be capable of uniting national identity and universal projection. In articles such as “El folklore en la creación musical panameña” (1952) and “Contra el cutarrismo en nuestra música” (1978), he reveals his rejection on nationalism based on folkloric citations and his defense of an art based on technical authenticity and the creative transformation of folklore. In texts such as “Nacionalismo versus Dodecafonismo” (1959) y “El público y la música viva” (1975), Cordero argues that modern technique –including dodecaphonism– is not contrary to the national spirit, but rather a means of expressing Latin American sensibility with rigor and contemporaneity. His musical journalism presents one of the great Latin American modernist dilemmas of the epoch: the search for a synthesis between national authenticity, technical discipline, and aesthetic universality.Editorial HistoryReceived: November 7, 2025Accepted: December 18, 2025
Keywords: Roque Cordero; musical journalism; nationalism; universalism; twelve-tone music